Trifluoromethyl‐Group Bearing, Hydrophobic Bulky Cations as Defect Passivators for Highly Efficient, Stable Perovskite Solar Cells. Issue 12 (5th November 2021) - Lee, Hock Beng; Kumar, Neetesh; Devaraj, Vasanthan; Tyagi, Barkha; He, Siwei; Sahani, Rishabh; Ko, Keum-Jin; Oh, Jin-Woo; Kang, Jae-Wook
Abstract : Solution‐processed perovskite films are rich in surface defects and grain boundaries, which limits their performance and stability in photovoltaic application. Surface passivation using bulky organic cations can effectively reduce the surface defects of a perovskite film without affecting its fundamental properties. Herein, the use of hydrophobic bulky aromatic molecules, namely 4‐trifluoromethyl‐benzylammonium iodide/bromide (CF3 BZA‐I/Br), as defect‐passivators to heal the surface defects and grain boundaries of perovskite films is introduced. Owing to the presence of the trifluoromethyl (CF3 ) moieties, CF3 BZA‐I/Br‐passivated perovskite films exhibit a hydrophobic surface with significantly fewer grain boundaries. By suppressing the surface and interfacial imperfections, CF3 BZA‐Br‐treated perovskite solar cells achieve an outstanding power conversion efficiency (PCE) of 20.75%. The PCE improvement originates mainly from the reduction of trap states and nonradiative carrier recombination. The ultrathin hydrophobic barrier layer formed after passivation also shields the perovskite film surface from moisture ingress and environmental degradation, leading to improved stability of the devices. By optimizing the passivation conditions, the bulky CF3 BZA‐I/Br molecules could be the ideal defect passivators, with versatile applications in a wide variety of perovskite optoelectronics. Abstract : Herein, the authors demonstrate the use of bulky‐sized, trifluoromethyl‐group (CF3 ) bearing benzylammonium iodide (CF3 BZA‐I) and bromide (CF3 BZA‐Br) molecules as surface passivators for formamidium‐methylammonium‐based perovskite films. CF3 BZA‐I/Br passivated perovskite films exhibit larger grain size, lesser surface defects, and hydrophobic surface. The champion perovskite solar cell achieves an efficiency of ≈20.8% with significantly improved air‐ and photostability.